Influence of Stimulation Location and Posture on the Reliability and Comfort of the Nociceptive Flexion Reflex - Gwyn N Lewis; David A Rice; Kathryn Jourdain; Peter J McNair (Pain Research and Management)
BACKGROUND: The lower limb nociceptive flexion reflex (NFR) is commonly used to assess the function of the nociceptive system. Currently, there is a lack of standardized stimulation procedures to determine the NFR threshold, making comparisons of thresholds across studies difficult.